2000
DOI: 10.1091/mbc.11.6.1989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Family of Nonclassic Yeast Phosphatidylinositol Transfer Proteins Whose Function Modulates Phospholipase D Activity and Sec14p-independent Cell Growth

Abstract: Yeast phosphatidylinositol transfer protein (Sec14p) is essential for Golgi function and cell viability. We now report a characterization of five yeast SFH (Sec Fourteen Homologue) proteins that share 24 -65% primary sequence identity with Sec14p. We show that Sfh1p, which shares 64% primary sequence identity with Sec14p, is nonfunctional as a Sec14p in vivo or in vitro. Yet, SFH proteins sharing low primary sequence similarity with Sec14p (i.e., Sfh2p, Sfh3p, Sfh4p, and Sfh5p) represent novel phosphatidylinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
230
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(241 citation statements)
references
References 55 publications
11
230
0
Order By: Relevance
“…Consistent with this suggestion, increased expression of Shf2p and Shf4p, yeast PITPs that display PtdIns-but not PtdCho-transfer activity in vitro, can rescue the growth and secretory defects of sec14 mutants and requires the function of Spo14p to do so (Li et al, 2000). However, Sec14p itself exhibits both PtdCho and PtdIns transfer activity in vitro (Bankaitis et al, 1990), and the results of genetic analyses have not supported a model in which the essential vegetative function of Sec14p is to provide for activation of Spo14p (Sreenivas et al, 1998;Xie et al, 1998), because unlike sec14⌬ mutants, spo14⌬ mutants are viable (Honigberg et al, 1992;Rose et al, 1995).…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Consistent with this suggestion, increased expression of Shf2p and Shf4p, yeast PITPs that display PtdIns-but not PtdCho-transfer activity in vitro, can rescue the growth and secretory defects of sec14 mutants and requires the function of Spo14p to do so (Li et al, 2000). However, Sec14p itself exhibits both PtdCho and PtdIns transfer activity in vitro (Bankaitis et al, 1990), and the results of genetic analyses have not supported a model in which the essential vegetative function of Sec14p is to provide for activation of Spo14p (Sreenivas et al, 1998;Xie et al, 1998), because unlike sec14⌬ mutants, spo14⌬ mutants are viable (Honigberg et al, 1992;Rose et al, 1995).…”
Section: Introductionsupporting
confidence: 53%
“…That the suppression by SFH2 or SFH4 is dependent on Spo14p indicates that Spo14p PLD activity can substitute for Sec14p under these conditions. This may be due to activation of Spo14p through enhanced PtdIns(4,5)P 2 generation, as observed in Sec14 bypass conditions (Li et al, 2000), and may be a consequence of Spo14p-dependent PtdCho cleavage mimicking Sec14p-PtdCho transport function.…”
Section: Phosphoinositide Function During Meiosismentioning
confidence: 94%
See 1 more Smart Citation
“…Li et al, 2000), we further investigated the relationship between the Sec14 domain of LjPLP-IV and the yeast Sec14 protein on a functional level.…”
Section: The Ljplp-iv Sec14p-like Domain Complements a Yeast Sec14 Mumentioning
confidence: 99%
“…Studies in a number of eukaryotic systems have demonstrated that PITPs function to regulate various aspects of lipid metabolism (reviewed in Cleves et al, 1991; B.G. Li et al, 2000), but the first clue about their significance in vivo emerged from studies of Saccharomyces cerevisiae (Novick et al, 1980;Bankaitis et al, 1989Bankaitis et al, , 1990Aitken et al, 1990) showing their essential role in the formation of secretory vesicles and in protein transport from the Golgi complex. In vitro studies in mammalian systems have suggested that PITPs play important roles in promoting the activities of various inositol lipid-signaling pathways by regulating the production of certain phosphoinositides (Hay and Martin, 1993;Hay et al, 1995;Ohashi et al, 1995;Cunningham et al, 1996;Jones et al, 1998;Simon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%